(untitled) (International Journal of Current Engineering and Technology, 2014)
The present study focus on green chemistry in the synthesis of Zinc Oxide nanoparticles by Zinc nitrate and utilizing the bio components of leaves extract of Hibiscus rosa-sinensis. The Zinc Oxide nanoparticles are known to be one of the multifunctional inorganic nanoparticles and Zinc Oxide crystallites have been synthesized by simple and ecofriendly method. There is a growing attention to biosynthesis the metal nanoparticles using organisms. Among these organisms ,plants seem to be the best candidate and they are suitable for large scale biosynthesis of nanoparticles.Nanoparticles produced by plants are more stable, and the rate of synthesis is faster than that in the case of other organisms.The particle size and morphology of the synthesized nanoparticles is characterized by using Scanning Electron Microscope(SEM), and X-ray Diffraction(XRD).